2014
DOI: 10.1017/s1355617714000551
|View full text |Cite
|
Sign up to set email alerts
|

Early Neuropsychological Characteristics of Progranulin Mutation Carriers

Abstract: Mutations in the progranulin gene (GRN) are a common cause of familial frontotemporal dementia. We used a comprehensive neuropsychological battery to investigate whether early cognitive changes could be detected in GRN mutation carriers before dementia onset. Twenty-four at-risk members from six families with known GRN mutations underwent detailed neuropsychological testing. Group differences were investigated by domains of attention, language, visuospatial function, verbal memory, non-verbal memory, working m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…Furthermore, results from the GENFI study predicted that GRN + subjects would not show significant reduction in cortical volumes until approximately five years prior to illness onset, in which case, our GRN + subjects (on average eight years prior to predicted onset) might still be too early to demonstrate significant atrophy. However, it is interesting that both GENFI and a previous study of ours found that GRN + subjects demonstrate cognitive and neuropsychological deficits as well as changes in glucose metabolism as early as 10 years prior to illness onset ( Rohrer et al, 2015 ; Jacova et al, 2013 ; Hallam et al, 2014 ; Nasreddine et al, 2005 ); suggesting that the subtle decline in function precede obvious structural gray matter changes in the GRN + genetic subgroup. Finally, it is important to recognize that FTD represents a broad clinical spectrum with striking heterogeneity in the clinical features at the time of presentation, even among members of a family carrying a specific mutation.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Furthermore, results from the GENFI study predicted that GRN + subjects would not show significant reduction in cortical volumes until approximately five years prior to illness onset, in which case, our GRN + subjects (on average eight years prior to predicted onset) might still be too early to demonstrate significant atrophy. However, it is interesting that both GENFI and a previous study of ours found that GRN + subjects demonstrate cognitive and neuropsychological deficits as well as changes in glucose metabolism as early as 10 years prior to illness onset ( Rohrer et al, 2015 ; Jacova et al, 2013 ; Hallam et al, 2014 ; Nasreddine et al, 2005 ); suggesting that the subtle decline in function precede obvious structural gray matter changes in the GRN + genetic subgroup. Finally, it is important to recognize that FTD represents a broad clinical spectrum with striking heterogeneity in the clinical features at the time of presentation, even among members of a family carrying a specific mutation.…”
Section: Discussionmentioning
confidence: 63%
“…All subjects underwent genetic analysis to establish whether they were carriers of their family's mutation; however, the subjects and the investigators performing the clinical assessments remained blinded to the genetic results. Some features of the cohort have been described previously ( Jacova et al, 2013 ; Hallam et al, 2014 ). Participants underwent a detailed neurological examination and were screened for cognitive deficits with various scales including the mini mental state examination (MMSE) ( Folstein et al, 1975 ; Folstein et al, 1983 ), Frontal Assessment Battery (FAB) ( Dubois et al, 2000 ), and the Frontal Behavioral Inventory (FBI) ( Kertesz et al, 2000 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, the measurable functional and structural brain abnormalities in mutation carriers revealed in this review are likely to result in at least subtle or mild symptoms on sensitive clinical tests. In fact, neuropsychological group differences compared to controls have been observed in GRN and MAPT mutation carriers[8, 40]. There have been reports of premorbid psychiatric diagnoses in GRN mutation carriers[40].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we utilized the existing neuroimaging evidence to map out emerging brain abnormalities in predementia FTD- GRN . We use the term “predementia” to refer to asymptomatic mutation carriers, as well as those displaying early symptoms that fall short of meeting FTD diagnostic criteria[7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…The Movement Disorder Society Task Force Guidelines were used to design the battery of clinical tests for Parkinson's disease patient cohort. The test battery was chosen to overlap as much as possible with several large-scale provincial initiatives (i.e., CIMA-Q 35 ONDRI 36 ) and several provincial disease-specific studies (FTD in British Columbia 37 and Parkinson's disease in Alberta 38 ). The battery requires between 2 and 3 h to administer.…”
Section: Neuropsychological Evaluationmentioning
confidence: 99%